Eccentric operation of STATCOM using Predictive Controller - K. Varalakshmi; Narasimham R.L.; G. Tulasi Ramdas (International Journal of Power Electronics and Drive Systems (IJPEDS), 2018)
The impact of multilevel converter STATCOM in transmission and distribution system is given high importance. Increment of number of switches in multi-level cascaded H-bridge converter, made it more vulnerable to open circuit and short circuit faults. To reduce the effect of faults on line voltage magnitude, in this paper an advanced improved predictive controller is used to generate PWM pulses for the power electronic devices. A Cascaded H-bridge STATCOM, interconnected to a distribution system with linear and non-linear loads. The feedback control structure of STATCOM has an advantage of reducing THD and controllable reactive power. A switch fault detection and elimination method is proposed with a bypass switch connected to each H-bridge to surpass the faulty  H-bridge. The complete analysis with all control structures is designed in MATLAB/Simulink representing dynamic graphs and feasibility of proposed method is verified.